Pemeriksaan Gula Darah Sewaktu untuk Hidup Sehat - Zita Atzmardina; Ni Kanaya; Erick Makarau; Winnie Arnissa Chen; Kristin Nadia Berliani (jurnal ABDIMAS Indonesia, 2025)
Tuberculosis is a serious health problem and is one of the 10 leading causes of death globally. Tuberculosis can be influenced by medical and non-medical risk factors. Medical risk factors that play a role are patients with HIV positive or other immunocompromised diseases such as diabetes mellitus. Therefore, this activity aims to conduct blood sugar screening so that risk factors for tuberculosis can be identified. The method used is by taking blood to determine glucose levels and counseling to increase respondent knowledge. The results obtained were that all respondents had undergone GDS (Random Blood Sugar) examinations and there was an increase in respondent knowledge after counseling. It is hoped that this activity can take place routinely so that risk factors for tuberculosis can be reduced